PENINGKATAN NILAI KALOR BIOBRIKET CAMPURAN KULIT METE DAN DOMINANSI SEKAM PADI DENGAN METODE PIROLISA - Resha Widya Permana Putra; Arijanto Arijanto; Muchammad Muchammad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2013)
Biomass is an alternative fuel that can replace the role of coal, but it has not been widely used because of low calorific value and less valuable form . Thus briquetting and pyrolysis are answers to the problem. Pyrolysis is a thermochemical decomposition of organic material at elevated temperatures between 300 0C - 500 0C, without participation of oxygen. Biomass materials, widely available in Indonesia, are rice husks, cocoa shells, and cashew shells. The purposes of this study were to determine the effect of pyrolysis process, to increase the calorific value and to compare the results of biobriquette calorific composition value of 75% cashew shell - 25% rice husk by torefaction testing and pyrolysis testing with pyrolysis of biobriquette 75% rice husk - 25% cashew shell . The biomass was then formed into biobriquette to increase the density of the mass. Biobriquette materials used in this study were rice husk and cashew shell. Mass composition between cashew shell and rice husk was 50% - 50%, 75% -25%, and 100% glued together using PVA glue. Then they were formed into briquettes with 25-30 mm high and 25 mm in diameter with direct sunlight drying for 24 hours. Next, variations of pyrolysis temperature 325 0C, 350 0C and 375 0C were carried out within ranges of time of 15 minutes, 30 minutes, and 45 minutes. The highest increased calorific value was at 375 0C within time duration of 45 minutes was 5401.9 cal / g. In addition, the percentage of weight loss occured at 100% biobriquette composition of rice husk weight which decreased by 57.99%. Compared to torefaction and pyrolysis testings with different variations before, both testings produced the best calorific value of 6368.54 cal / g by testing biobriquette 75% cashew shell - 25% rice husk at pyrolysis temperature of 300 0C.